Risk of malignancy in pancreatic cysts with cytology of high‐grade epithelial atypia. Issue 9 (26th September 2018) - Hoda, Raza S.; Lu, Ree; Arpin, Ronald N.; Rosenbaum, Matthew W.; Pitman, Martha B.
Abstract : Background: The risk of malignancy is weighed against the attendant risks of surgery in the clinical management of pancreatic cysts. The latter are a group of histologically diverse and prognostically variable entities, and the risk of malignancy therein is primarily based on imaging characteristics—with or without high‐grade atypia. Cytologic criteria for high‐grade atypia in intraductal papillary mucinous neoplasms have recently been defined, and its recognition in all pancreatic cysts may help to guide management. Methods: All patients who underwent endoscopic ultrasound–guided fine‐needle aspiration for a pancreatic cyst at Massachusetts General Hospital from June 2015 to October 2016 were prospectively evaluated. Clinical data, radiographic impressions, biochemical analyses, and cytologic diagnoses of 118 pancreatic cyst fine‐needle aspiration biopsy specimens from 106 patients were reviewed. Clinical and radiologic data were used as follow‐up for 86 patients, and histology was obtained in 20 cases. Cysts were classified by imaging as high‐risk, worrisome, or low‐risk as defined by the 2012 Fukuoka consensus guidelines. Cytology was categorized as low‐grade or high‐grade. Malignant histology included mucinous cysts with high‐grade dysplasia, invasive adenocarcinomas, and neuroendocrine tumors. The risk of malignancy (ROM) was determined by histological outcome. Results: The presence of high‐grade cytology ( P < .01) was the only statistically significant predictor of malignancy and was 89% sensitive and 98% specific for malignancy. The positive predictive value (ie, ROM) of high‐grade atypia on cytology was 80%. Conclusions: High‐grade atypia is both sensitive and specific for identifying high‐risk pancreatic cysts and is associated with a high risk of malignancy, and thus resection is warranted. Abstract : The cytologic criteria for high‐grade atypia in intraductal papillary mucinous neoplasms have recently been defined, and its recognition in all pancreatic cysts may help to guide management. This prospective study shows that the presence of high‐grade atypia is both sensitive and specific for identifying pancreatic cysts with an 80% risk of malignancy, and thus surgical resection is warranted.